Trends in the brain-computer interface - Kostrec, Matej; Štědroň, Bohumír (Acta Universitatis Carolinae. Kinanthropologica, 2021)
The goal of every human being on our planet is to improve the living conditions not only of his life, but also of all humanity. Digitization, dynamic development of technological equipment, unique software solutions and the transfer of human capabilities into the form of data enable the gradual achievement of this goal. The human brain is the source of all activities (physical, mental, decision-making, etc.) that a person performs. Therefore, the main goal of research is its functioning and the possibility to at least partially replace this functioning by external devices connected to a computer. The Brain-Computer Interface (BCI) is a term which represents a tool for performing external activities through sensed signals from the brain. This document describes various techniques that can be used to collect the neural signals. The measurement can be invasive or non-invasive. Electroencephalography (EEG) is the most studied non-invasive method and is therefore described in more detail in the presented paper. Once the signals from the brain are scanned, they need to be analysed in order to interpret them as computer commands. The presented methods of EEG signal analysis have advantages and disadvantages, either temporal or spatial. The use of the inverse EEG problem can be considered as a new trend to solve non-invasive high-resolution BCI.
Keywords: Evoked Potentials, Visual; rozhraní mozek-počítač; zrakové evokované potenciály; Electroencephalography; Diagnostic Techniques, Neurological; Electrooculography; blízká infračervená spektroskopie; magnetická rezonanční tomografie; Positron-Emission Tomography; elektroencefalografie; pozitronová emisní tomografie; Neuroimaging; diagnostické techniky neurologické; neurozobrazování; Brain-Computer Interfaces; lidé; Humans; elektrookulografie; Magnetic Resonance Imaging; magnetoencefalografie; Magnetoencephalography; Spectroscopy, Near-Infrared